PENERAPAN METODE MONTESSORI DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SD - Resti Hidayat; Putri Fajriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Montessori method, created by Maria Montessori, emphasizes learning through physical activities and organizing the learning environment to match the developmental stages of the child. In this study, the Montessori method is used to improve the early reading skills of students in lower elementary school grades. Literature review was used to analyze the content of various relevant sources. The research results show that the Montessori method is effective in improving students' early reading skills. This method uses special materials such as sandpaper letters and movable uppercase letters, which help children become more familiar with letters and sounds.